The Effect Of QRIS Implementation, Financial Report Quality, And Financial Literacy On The Performance Of Msmes In Palu City - Rahmawati, Zaskia; Zainuddin, Fatlina; Munawarah, Munawarah; Fera, Fera (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2026)
The aim of this research is to identify and analyze: (1) the effect of implementing QRIS (Quick Response Code Indonesian Standard) on the performance of SMEs in Palu city, (2) the effect of financial report quality on the performance of SMEs in Palu city, (3) the effect of financial literacy on the performance of SMEs in Palu city. The type of research used is quantitative (indicating relationships between variables). The population in this study consists of SMEs in Palu city that use QRIS (Quick Response Code Indonesian Standard). The sampling technique in this study used the Slovin formula, with a total of 98 respondents. Data collection was conducted using questionnaires and direct interviews with MSMEs. The analytical method used was multiple linear regression analysis using the Smart-PLS4 application. The results of the study indicate that (1) there is an effect of the implementation of QRIS (Quick Response Code Indonesian Standard) on the performance of MSMEs in Palu city, (2) there is an effect of the quality of financial reports on the performance of MSMEs in Palu city, and (3) there is an effect of financial literacy on the performance of MSMEs in Palu city.